Microfinance - interregional comparison - Harmincová, Zuzana; Janda, Karel; Zetek, Pavel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
In the introduction of the master thesis, the historical development and the reasons for the emergence of microfinance are described. The thesis focuses on comparison of the functioning of microfinance in various developing regions of the world, as well as on the analysis of the overall functioning, effectiveness, strengths and weaknesses, potential threats and opportunities in the microfinance markets. The conclusion offers several possibilities and insights on how microfinance could be more efficient in financial terms. The thesis also presents a brief evaluation of the benefits of microfinance and based on findings provides a prediction of further development of microfinance.
Vedoucí práce: Karel Janda
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses